Relationship between Work Environment, Leadership Style, Performance Appraisal, and Employee Turnover in Hebei, China - Chen, Bixin (2016)
Hebei is a large province in China, the economy of Hebel is in rapid developing. Currently, there are 9597 thousand employees working in Hebei (Iqbal et al, 2015). However, the problem of high employee turnover was happened with the economic development in Hebei. Therefore, the purpose of this study is to examine the relationship between work environment, leadership style, performance appraisal and employee turnover in Hebei, China. According to Thatcher et al. (2006), Khan (2014), Hwang & Chang (2009), Chen et al. (2007), Chandra & Priyono (2016), Chouhan et al. (2016), the great work environment, apposite leadership style and opportune performance appraisal, these factors enable companies to better retain employees. The research methodology is used correlation which is a quantitative survey to study the relationship between the independent and dependent variables in order to get the extent of the relationship whether the relationship exist. The data collection had been conducted through online questionnaire and 384 respondents had been acquired with the snowball sampling method. From the research findings, the work environment, leadership style and performance appraisal have the significant influence with employee turnover, and the leadership style has the highest influence towards the employee turnover. Therefore, all the factors will have a significant relationship towards the employee turnover in Hebei, China.